Construction of a competition practice system for robotics engineering based on a competency model. Issue 3 (14th January 2022) - Zhang, Ziqiang; Ning, Meng; Wu, Zhi; Liu, Chunqi; Li, Jun
Abstract: Competition practice is of great significance for improving the engineering ability of undergraduates majoring in robotics engineering, and it occupies an important position in practical teaching systems. However, most existing competitions are spontaneously participated by students, and problems, such as poor systemicity, unclear ability‐training goals, and lack of an effective evaluation system, occur, resulting in limited improvement in students' ability. In this paper, a competency model for robotics engineering was proposed. It includes four dimensions: knowledge, skills, dispositions, and evaluation. The first three dimensions comprise multiple secondary and tertiary indices. On this basis, a competition practice system was established. The system includes four practical course groups and a final competition, and the competency model runs through before, during, and after practice. The competition practice system based on the competency model was applied to two groups of students. The analysis results show that students have a clear understanding of their own ability, and their comprehensive ability has been improved. This finding provides a reference for the construction of practice systems for other engineering majors.